2018
DOI: 10.1021/acs.analchem.8b01681
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Nanochannel-Based Interferometric Sensor for Selective Detection of Polar and Aromatic Volatile Organic Compounds

Abstract: Public awareness of the toxicity of volatile organic compounds (VOCs) has led to increased requirements for direct measurement of these substances. This work reports the sensitive detection of VOCs at the ppb level by an interferometric sensor based on the multilayer silica-nanochannel membrane (MSNM). The MSNM is fabricated by layer-by-layer stacking of a free-standing ultrathin SNM composed of regularly ordered channels with an ultrasmall diameter of about 2.3 nm and an ultrahigh density of about 4 × 10 cm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Similar to the biological nanochannels in living systems, the biomimetic stimuli‐responsive nanochannels also show some characteristics such as ion selectivity, ion rectification and ion gating, which can be used in many fields including biosensors, and drug delivery .…”
Section: Applications Of Biomimetic Stimuli‐responsive Nanochannelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the biological nanochannels in living systems, the biomimetic stimuli‐responsive nanochannels also show some characteristics such as ion selectivity, ion rectification and ion gating, which can be used in many fields including biosensors, and drug delivery .…”
Section: Applications Of Biomimetic Stimuli‐responsive Nanochannelsmentioning
confidence: 99%
“…(A) Supersandwich structure‐based nanopore sensors for detecting ATP and DNA; (B) Schematic description of the hour‐glass shaped sensor for glucose detection; (C)Scheme description of a novel nanodevice by decorating continuous Au nanoparticles with three geometric dimensions on the inner surface of channels in AAO membranes; (D) Sketch map of detecting miR‐204 and miR‐210 sensor based on solid nanopores; (E) Schematic illustration of device for detecting retinol and AA in fruit juices based on mesochannels on the electrode surface and DPVs of CM@SMA/ITO and SMA/ITO electrodes in untreated commercial orange juice before and after the addition of 2 mM AA; (F) Schematic illustration of volatile organic compound detection by multilayer silica‐nanochannel membrane‐based interferometry. (a) Reproduced with permission from , copyright 2013, Wiley‐VCH; (b) Reproduced with permission from , copyright 2014, American Chemical Society; (c) Reproduced with permission from , copyright 2015, Wiley‐VCH; (d) Reproduced with permission from , copyright 2017, American Chemical Society; (e) Reproduced with permission from , copyright 2016, American Chemical Society; (f) Reproduced with permission from , copyright 2018, American Chemical Society.…”
Section: Applications Of Biomimetic Stimuli‐responsive Nanochannelsmentioning
confidence: 99%
See 2 more Smart Citations
“…PMs which exhibit luminescent chromism in response to exposure to vapors of volatile organic compounds (VOCs), especially, are attractive materials for detecting a small amount of leakage of toxic or explosive gases and for security ink. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, these compounds possess potential instability toward the air, moisture, and/or other harsh chemical conditions, and therefore a growing number of studies have recently reported chemically and physically stable PMs. [32,33] Nonporous molecular crystals (NMCs), on the other hand, have no such functional voids in their packing patterns because of the absence of the polymeric or supramolecular structures derived from continuous valence, coordination, or hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%